Inhibition of thyroid-restricted genes by follicular thyroglobulin involves iodinated degree - Huang, Huibin; Shi, Yaxiong; Lin, Ling; Li, Liangyi; Lin, Xiahong; Li, Xisheng; Xu, Dongming (Journal of cellular biochemistry, 2011)
Follicular thyroglobulin (TG) reflects the storage of both iodine and thyroid hormone. This is because it is a macromolecular precursor of thyroid hormone and organic iodinated compound in follicular lumen. Thus, it may have an important feedback role in thyroid function. In this study, monolayer cells were cultured and follicles were reconstituted with primary pig thyroid cells in vitro. Reconstituted follicles were treated with iodine and methimazole (MMI), a drug that blocks iodine organification and reduces the degree of TG iodination in follicular lumen. The high degree of iodinated TG in follicular lumen was observed to inhibit thyroid‐restricted gene expression. To confirm this finding, monolayer thyroid cells were treated with a different degree of TG iodination at the same concentration. These iodinated TG were extracted from reconstituted follicles of different groups. In this manner, this study provides firsthand evidence suggesting that follicular TG inhibits the expressions of thyroid‐restricted genes NIS, TPO, TG, and TSHr. J. Cell. Biochem. 112: 971–977, 2011. © 2011 Wiley‐Liss, Inc.